Establecimiento de alternativas de aprovechamiento de los residuos del pescado viables para la comunidad pesquera de la playa de Caño dulce-Tubará (2022)
The generation of fishing waste in Colombia is one of the topics with less research development, due to the scarce use of this type of waste. The waste of fish waste on the beach of Caño Dulce and the consequent deterioration in the environment generated the development of this research that had as its objective, to determine alternatives for the use of fish waste in the artisanal fishing community of Caño Beach. Sweet- Tubará. For its development, bibliographical information was collected that allowed identifying alternatives for use, applicable to the socioeconomic and environmental conditions present in these types of fishing communities, such as biological silage, fish emulsion and biogas, which are generated by the fermentation of the fish waste; Likewise, in order to establish the most viable alternative, instruments and techniques for collecting information such as surveys and interviews were applied, also considering the knowledge derived from the cultural tradition of the fishing community, constituting these "experts" who validate the alternative of use more appropriate to their current conditions. According to the results obtained by the community, the alternative that best suits their demands is biogas, as it becomes a mechanism to solve the shortcomings of the socioeconomic and environmental aspects present in this population of artisanal fishermen from Caño Dulce. - Tubará -Atlantic